Utilization of Zoom Cloud Meeting Application as a Medium of Da'wah and Spiritual Guidance in Hospital Settings - Laela, Faizah Noer; Izzah, Rizqi Amaliatul (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The aim of this research is highly relevant to current conditions, namely to examine the use of the Zoom Cloud Meeting application as a service for da'wah and spiritual guidance in a hospital environment. This research adopts a qualitative descriptive method. In line with this approach, the study applies descriptive qualitative analysis, which means that specific findings obtained during the research are collected and abstracted. The results of this study indicate that the use of Zoom Cloud Meeting facilitates communication between patients’ families—especially those in the ICU who cannot be visited—and patients themselves. The spiritual guidance process conducted by counselors consists of several stages: Muqaddimah (opening greetings by the Islamic spiritual guide to build rapport with patients and their families), recitation of prayers from the Qur’an and Sunnah, delivering advice through tausiyah as mental strengthening, and closing with positive impressions for the patients. Beyond that, spiritual guidance also aims to help patients heal from a spiritual perspective by providing motivation and encouragement while reminding them that health and illness come from God